Strategi Pengembangan Agribisnis Komoditas Kunyit Kuning (Studi Kasus di Desa Kesamben Wetan, Kecamatan Driyorejo, Kabupaten Gresik, Jawa Timur): Turmeric Commodity Agribusiness Development Strategy (Case Study in Kesamben Wetan Village, Driyorejo District, Gresik Regency, East Java) - Angul, Vantria; Daryanto, Didik (Jurnal Ilmiah Manajemen Agribisnis, 2023)
This study aims to identify internal and external factors that impact the unheroic turmeric agribusiness development strategy, formulate druthers in the Turmeric Agribusiness Development Strategy in Kesamben Wetan village, Driyorejo district, gersik regency. The system used is the qualitative system. the exploration position intentionally is Kesamben Wetan village. The logical system used is turmeric farmer analysis to identify internal and external factors that impact the unheroic turmeric development strategy swot analysis in the form of a swot matrix which describes internal conditions, videlicet strengths and sins, as well as external conditions, videlicet openings and pitfalls faced by turmeric growers in Kesamben Wetan village, from the results of internal factor assessmentit has been shown that turmeric agribusiness in Kesanben Wetan village, Driyorejo district, Gresik regency has a strength (strengths) of 0.69 compared to sins (sins). the results of the assessment of external factors have shown that the unheroic turmeric agribusiness in Kesamben Wetan village, Driyorejo district, gresik regency has an advantage (openings) of 0.42 points compared to the pitfalls (pitfalls) faced. The results attained in this study indicate that the unheroic turmeric agribusiness in kesamben wetan village, driyorejo district, gresik regency is in quadrant i ( so), videlicet progressive, so that the unheroic turmeric agribusiness in gresik regency can apply a growth exposure strategy by expanding turmeric marketing to new areas and piercing request.